Pengaruh Penggunaan Smartphone terhadap Minat Belajar Siswa Kelas XI di Madrasah Aliyah Negeri 1 Sijunjung Tahun Pelajaran 2023/2024 - Oktavia, Anggi Windi; Fitria, Linda; Wijaya, Indra (YASIN, 2024)
The aim of this research is to determine the effect of smartphone use on class XI students' interest in learning at MAN 1 Sijunjung. This type of research is case study research. The research was carried out in 2024. The population of this research was class XI students at MAN 1 Sijunjung. The total population was 115 students. Data was collected using a questionnaire and tested using simple linear regression analysis. The independent variable was smartphone use, while the dependent variable was students' interest in learning. The data analysis technique used is the prerequisite analysis test which includes normality test and linearity test, simple linear regression test and hypothesis test. The research results show that: Based on the results of research analysis regarding simple linear regression calculations between smartphone use and interest in learning, it is known that the significant value is 001<0.05, which means that smartphone use has an effect on interest in learning. Based on the calculation, the correlation between smartphone use and interest in learning is rcount>rtable (0.572>0.181), so it can be said that there is a positive and significant relationship between variable X (smartphone use) and variable Y (interest in learning). Therefore, the proposed hypothesis is declared accepted.